BARGAINING POSITIONS OF WOMEN & FEMALE CANDIDATES IN POLITICAL CONTESTATION - Chalid Tualeka (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
After 25 years of reform and several elections, the 30% quota for women's representation as legislators - both at the national level (DPR RI), as well as at the regional level (Provincial DPRD) and Regency/City DPRD, can be said to have never been fulfilled. In the 2019 election, women's representation in the DPR RI only reached 20.8% or 120 people out of the 575 members of the DPR RI. This fact, of course, raises questions. The fact that several elections have taken place and the level of women's representation in parliament (central/regional DPR) has not yet reached the ideal minimum level (30%) is an interesting phenomenon and needs to be explained. Through this study, the researcher/author tries to analyze and explain this phenomenon from the perspective of Classical Sociology , namely from a Marxist, Durkheimian and Weberian perspective. By analyzing the problem using a sociological approach, it is intended to provide a theoretical and empirical picture of